A test for within‐lake niche differentiation in the nine‐spined sticklebacks (Pungitius pungitius). Issue 14 (14th June 2016) - Calboli, Federico C. F.; Byström, Pär; Merilä, Juha
Abstract: Specialization for the use of different resources can lead to ecological speciation. Accordingly, there are numerous examples of ecologically specialized pairs of fish "species" in postglacial lakes. Using a polymorphic panel of single nucleotide variants, we tested for genetic footprints of within‐lake population stratification in nine‐spined sticklebacks ( Pungitius pungitius ) collected from three habitats ( viz . littoral, benthic, and pelagic) within a northern Swedish lake. Analyses of admixture, population structure, and relatedness all supported the conclusion that the fish from this lake form a single interbreeding unit. Abstract : Ecologically specialized sympatric forms of fish are relatively common in postglacial lakes, but few genetic tests have been conducted to detect such habitat‐associated differentiation. The first test for habitat‐associated genetic differentiation in nine‐spined sticklebacks uncovers no evidence for within‐lake population substructuring.